2005
DOI: 10.1152/ajprenal.00297.2004
|View full text |Cite
|
Sign up to set email alerts
|

Micropuncture determination of nephron function in mice without tissue angiotensin-converting enzyme

Abstract: . Micropuncture determination of nephron function in mice without tissue angiotensin-converting enzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 37 publications
2
42
1
Order By: Relevance
“…Previous micropuncture studies showed that the absence of tissue-bound ACE blunts the tubuloglomerular feedback mechanism response. 32 In addition, our mice lack endothelial ACE, perhaps reducing angiotensin II availability in the renal vasculature. The second and more important consideration is that modulation of glomerular hemodynamics and/or GFR by renal ACE plays an important role in the initial hypertensive response to L-NAME.…”
Section: Discussionmentioning
confidence: 97%
“…Previous micropuncture studies showed that the absence of tissue-bound ACE blunts the tubuloglomerular feedback mechanism response. 32 In addition, our mice lack endothelial ACE, perhaps reducing angiotensin II availability in the renal vasculature. The second and more important consideration is that modulation of glomerular hemodynamics and/or GFR by renal ACE plays an important role in the initial hypertensive response to L-NAME.…”
Section: Discussionmentioning
confidence: 97%
“…32 To determine kidney GFR and nephron filtration and reabsorption rates, mice were infused with 125 I iothalamate (Glofil; Questcor Pharmaceuticals, Hayward, CA) at about 40 Ci/h. End proximal segments were identified by injecting a bolus of artificial tubular fluid stained with FD&C green from a 3-to 4-m tip pipette.…”
Section: Hemoglobin A1cmentioning
confidence: 99%
“…From a recent study with differential genetic ablation of ACE in mice (17), it was concluded that local ANG II generation by renal tissue ACE is required for TGF. The massive TGF augmentation by pressure-dependent RAS changes observed in our experiments (Fig.…”
Section: Tubuloglomerular Feedback In Rbf Controlmentioning
confidence: 99%